2007
DOI: 10.1016/j.drugalcdep.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on psychomotor performance and perceived impairment in heavy binge social drinkers

Abstract: Alcohol intoxication often results in negative consequences; however, specific behavioral and subjective effects vary as a function of individual differences. The present study utilized an alcohol challenge paradigm to examine whether heavy binge social drinkers (HD; n=77), compared to light social drinkers (LD; n=55), exhibit: (1) greater tolerance in psychomotor task performance under the influence of alcohol, and (2) differential perceptions of the impairing effects of alcohol. The study included three test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
102
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 43 publications
8
102
0
Order By: Relevance
“…Previous research has indicated that visuomotor performance is affected by acute alcohol intoxication (Brumback et al, 2007), although this may be the case only for older drinkers. Animal model research implicates adolescence as a time in which individuals are insensitive to the motor-impairing aspects of alcohol (Ramirez and Spear, 2010;White et al, 2002), and our fi ndings could refl ect a similar insensitivity in our sample of underage youth.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has indicated that visuomotor performance is affected by acute alcohol intoxication (Brumback et al, 2007), although this may be the case only for older drinkers. Animal model research implicates adolescence as a time in which individuals are insensitive to the motor-impairing aspects of alcohol (Ramirez and Spear, 2010;White et al, 2002), and our fi ndings could refl ect a similar insensitivity in our sample of underage youth.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the binge drinkers reported feeling more stimulated by the 0.65 g ⁄ kg dose of alcohol compared to the nonbinge drinkers. Brumback et al (2007) also reported that binge drinkers felt less impaired by an acute dose of alcohol, despite similar levels of alcohol-induced impairment as lighter social drinkers on a digit-symbol substitution task and a grooved pegboard task. If binge drinkers are more stimulated by alcohol, they may feel more bravado and be more willing to drive, despite intoxication.…”
mentioning
confidence: 86%
“…Repeated exposure to alcohol may result in not only physiologic tolerance but behavioral tolerance, a neuroadaptive process resulting in a diminished behavioral response to a given alcohol level. While controlled studies of light to moderate drinkers have demonstrated the alcohol tolerance phenomenon, there has been scant scientific investigation of subjects who are chronic heavy drinkers who appear to have massive alcohol tolerance [15][16][17][18] The behavioral and subjective effects from any given alcohol level vary widely in the general population. Prior studies have demonstrated that moderate female drinkers of alcohol (about 35 drinks per month) demonstrated a reduced response to a given amount of alcohol ingestion compared to light drinkers (about seven drinks per month) and were viewed as less impaired following similar alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%